2017
DOI: 10.1155/2017/9057250
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Gas Sensing Using Palladium-Graphene Nanocomposite Material Based on Surface Acoustic Wave

Abstract: We report the fabrication and characterization of surface acoustic wave (SAW) hydrogen sensors using palladium-graphene (Pd-Gr) nanocomposite as sensing material. The Pd-Gr nanocomposite as sensing layer was deposited onto SAW delay line sensor-based interdigitated electrodes (IDTs)/aluminum nitride (AlN)/silicon (Si) structure. The Pd-Gr nanocomposite was synthesized by a chemical route and deposited onto SAW sensors by air-brush spraying. The SAW H2 sensor using Pd-Gr nanocomposite as a sensing layer shows a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Therefore, noble metal catalysts coated onto graphene have been used for H 2 sensing. Among different kinds of noble metal catalysts, the palladium (Pd) nanoparticle (NP) has been demonstrated as a good H 2 sensing material due to its high H 2 solubility at RT. Johnson et al reported chemical vapor deposition (CVD)-based multilayer graphene/Pd for H 2 sensing; however, the reported multilayer graphene nanoribbon was obtained through 800 °C thermal de-intercalation, the vacuum-filtration process, and anodic alumina (AAO) filter membranes, and therefore, it required a time-consuming and expensive process . Lupan et al introduced ultralight aerographite microtubes for H 2 sensing .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, noble metal catalysts coated onto graphene have been used for H 2 sensing. Among different kinds of noble metal catalysts, the palladium (Pd) nanoparticle (NP) has been demonstrated as a good H 2 sensing material due to its high H 2 solubility at RT. Johnson et al reported chemical vapor deposition (CVD)-based multilayer graphene/Pd for H 2 sensing; however, the reported multilayer graphene nanoribbon was obtained through 800 °C thermal de-intercalation, the vacuum-filtration process, and anodic alumina (AAO) filter membranes, and therefore, it required a time-consuming and expensive process . Lupan et al introduced ultralight aerographite microtubes for H 2 sensing .…”
Section: Introductionmentioning
confidence: 99%
“…As indicated in Fig. 5 c, with the presence of oxygen, the dissociated H 2 atoms react with oxygen and form water 34 , 40 . Then, the concentration of H 2 bounded by the sensitive layer decreases.…”
Section: Discussionmentioning
confidence: 94%
“…On the one hand, good electrical properties of graphene were given high consideration and the majority of H 2 sensors using graphene-like sensitive layers worked on account of the variation of conductivity induced by adsorbed H 2 5 , 27 – 31 . On the other hand, ultrasonic H 2 sensors using graphene-like sensitive layers were also presented 32 – 34 . By adopting Pd as a catalyzer, the sensitivity was increased from 5.8 kHz to 30 kHz towards 1% H 2 mixed in air at room temperature 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Sayago et al [89] reported high sensitivities of 3087 Hz/ppm to DMMP and 760 Hz/ppm to DPGME with the same type of sensitive material. A shift of 25 kHz to 0.5 % of H2 concentration was reported, with good repeatability and stability, by using a SAW platform associated with Pd-Gr nanocomposite [90]. Similarly, SWCNTs were investigated with SAW platform for the detection of ethyl acetate and toluene vapors with sensitivities of 5.45 kHz/ppm and 7.47 kHz/ppm, respectively [91], and a SWCNTs -Cu nanoparticles composite based SAW platform exhibited a sensitivity of 2.6 kHz/ppm to H2 gas [92].…”
Section: A Acoustic Waves Based Platforms For Chemical and Bio Sensing And Monitoringmentioning
confidence: 91%